DESIGN AND SIMULATION OF HEAT SINK FOR HIGH POWER ELECTRONICS USING CFD - S, Jeevaraj. (International Journal of Scientific Research and Management (IJSRM), 2013)
Recent trend towards higher power density and smaller package size in electronic systems demands an effective cooling mechanism in order to prevent the electronic components from overheating. The forced-air cooling technique, one of the effective methods for thermal management of electronic equipment cooling, is commonly used in a conventional-size heat sink. Conventional or mini sized heat sinks are commonly used in many industrial applications as cooling devices, because of their easy serviceability, high reliability, simplicity in the mechanism of heat transfer and ease of testing. In this paper heat sink is designed and analyzed for different velocity variation at the inlet to select appropriate fan to cool the heat sink and also effect of ambient conditions on the heat sink are studied finally the results are compared with the computational fluid dynamics software